2008
DOI: 10.1002/cncr.23235
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prostate‐specific antigen level at diagnosis on the relative survival of 28,531 men with localized carcinoma of the prostate

Abstract: BACKGROUND. To evaluate the predictive value of prostate‐specific antigen (PSA) in a population‐based cohort, the authors analyzed relative survival in all men with localized prostate cancer who were registered in the Swedish National Prostate Cancer Register (NPCR) from 1996 to 2005. METHODS. All men aged <75 years with localized tumors were identified in the NPCR. A Poisson regression analysis was performed using observed death as response and the expected death rate as offset. The expected and observed numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 18 publications
4
18
0
Order By: Relevance
“…Interestingly, though men in both the intermediate and highest glucose subgroups had poorer PCa outcomes. These findings may have important clinical implications for PCa detection and treatment, particularly among men with high glucose and low PSA levels, as previous evidence have shown that low PSA level is also concomitant with poorer PCa survival [61]. Overall, our findings further support a potential role for the lipid and glucose metabolism in prostate carcinogenesis.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, though men in both the intermediate and highest glucose subgroups had poorer PCa outcomes. These findings may have important clinical implications for PCa detection and treatment, particularly among men with high glucose and low PSA levels, as previous evidence have shown that low PSA level is also concomitant with poorer PCa survival [61]. Overall, our findings further support a potential role for the lipid and glucose metabolism in prostate carcinogenesis.…”
Section: Resultssupporting
confidence: 83%
“…This finding may be partly due to the fact that men with PSA <4 μg/L are not likely to be biopsied and may therefore be diagnosed in the symptomatic stage when the cancer is more aggressive or advanced. These results are also in line with other studies indicating that men with low-PSA producing cancers tend to develop very poorly differentiated or highly tumorigenic castration-resistant PCa cells [59][60][61].…”
Section: Glucosesupporting
confidence: 92%
“…Second, a declining PSA level was associated with a significantly increased risk of PCSM in the present cohort. This correlation between low serum PSA levels and high‐grade prostate cancer has been shown in other studies [18,27,28], and may reflect the decrease in PSA production due to hypogonadism [29] or from dedifferentiated high‐grade prostate cancer cells [30]. The biological mechanism to explain this later phenomenon remains unclear.…”
Section: Discussionsupporting
confidence: 62%
“…6 Nevertheless, some PCa patients with poor prognoses have a low PSA level. 7,8 The currently available clinicalpathological features, such as the Gleason grade group, clinical and pathological stage and surgical margin, 9,10 are unable to provide accurate predictions for biochemical recurrence. [11][12][13] Thus, it is crucial to develop an accurate prognostic signature to predict the recurrence risk for PCa patients after radical prostatectomy.…”
Section: Introductionmentioning
confidence: 99%